2020
DOI: 10.1111/ijlh.13319
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood morphology review and diagnostic proficiency evaluation by a new Spanish EQAS during the period 2011‐2019

Abstract: Introduction The Spanish Haematology and Haemotherapy Society organizes peripheral blood smear review scheme, focused on the evaluation of diagnostic proficiency of participants by blood cell morphology analysis. The objective was to evaluate the efficacy of this scheme as an educational tool to improve the diagnostic proficiency of the participants. Methods During 2011‐2019, 54 peripheral blood smears, alongside with patient details such as age, sex, blood cell counts and relevant clinical information, were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…With respect to ALC, external quality control programs have revealed the difficulties for their recognition by morphology, being the cells more difficult to identify by the participants 27 . In this work, we found that the MC‐80 is the first analyser capable of detecting ALC, since they were automatically identified in almost 50% of smears from patients with B‐LN (NOS), FL, MCL, and SMZL.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…With respect to ALC, external quality control programs have revealed the difficulties for their recognition by morphology, being the cells more difficult to identify by the participants 27 . In this work, we found that the MC‐80 is the first analyser capable of detecting ALC, since they were automatically identified in almost 50% of smears from patients with B‐LN (NOS), FL, MCL, and SMZL.…”
Section: Discussionmentioning
confidence: 87%
“…With respect to ALC, external quality control programs have revealed the difficulties for their recognition by morphology, being the cells more difficult to identify by the participants. 27 In this work, we found that the MC-80 is the first analyser capable of detecting ALC, since they were automatically identified in almost 50% of smears from patients with B-LN (NOS), FL, MCL, and SMZL. Although an improvement over previous technologies has been achieved with the MC-80, sensitivity for ALC automatic detection is very low and further advances in their automatic recognition is still needed.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Microscopy of stained peripheral blood smears still holds significant relevance in hematological studies [1][2][3]. This simple protocol requires the expertise of physicians, who provide the robustness and versatility of the human power of pattern recognition but, simultaneously, the protocol has the limitation of being time-consuming.…”
Section: Introductionmentioning
confidence: 99%